The Use of Fillers by Teachers in EFL Classroom Interaction - Aryarta, Anggih Restu; Ihsan, Mohamad Ahsanul; Wahyuni, Sri (Universitas Negeri Semarang, 2025)
Fillers have an important role in communication, especially for teachers to improve their delivery style and communication skills, resulting in a more positive and efficient classroom environment for the students. Fillers often used by teachers when speaking but it is possible that they do not know what fillers are and how to use them. This study aims to explain the kinds and functions of fillers used by teachers in EFL classroom Interaction. This study implements descriptive qualitative method. The participants are students of in-serviced teacher program in Universitas Negeri Semarang 2022. The data is analyzed using the theory of filler types by Rose (1998), which are lexicalized and unlexicalized. In addition, this study also uses theory of filler functions by Stenstrom (1994), which are hesitation, empathizer, mitigation, time-creating device, and editing term. This study found two types of filler namely, lexicalized and unlexicalized fillers. Filler okay is the most lexicalized filler frequently used by the teachers. Filler uh is the most unlexicalized filler frequently used by the teachers. Further, this study found five functions of filler used in EFL classroom interaction, such as hesitation in 99 utterances, empathizer in 49 utterances, mitigation in 20 utterances, time-creating device in 14 utterances, and editing term in 6 utterances.